2002
DOI: 10.1046/j.1365-2141.2002.03452.x
|View full text |Cite
|
Sign up to set email alerts
|

Allele and haplotype frequency at human leucocyte antigen class I/II and immunomodulatory cytokine loci in patients with myelodysplasia and acute myeloid leukaemia: in search of an autoimmune aetiology

Abstract: Summary.  An autoimmune mechanism in the␣pathogenesis of myelodysplastic syndrome (MDS) is suggested by response to immunosuppression, with CD8+ T‐lymphocytes implicated in the haematopoietic suppression. We therefore sought evidence for human leucocyte antigen (HLA) restriction and variant frequency differences in selected polymorphisms at␣the loci for the immunomodulatory cytokines, tumour necrosis factor α (TNF‐α), lymphotoxin‐α (LT‐α) and interleukin 10 (IL‐10) in patients with MDS and acute myeloid leukae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
1
5
2
1
Order By: Relevance
“…Although neither the IL10À1082 nor the IL10À592 promoter polymorphism alone predicted response to treatment, the IL10 ACC/ACC diplotype was associated with SVR and this association was relatively strong, especially after adjustment for other predictors of SVR. We also note that the frequency of ACC/ACC diplotype among the HALT-C population (5.8%) was lower than that observed in the general adult population by Trompet (7.3%), Gowans (7.8%) and Klein (10%) [28][29][30] suggesting that subjects with this diplotype were underrepresented in the HALT-C cohort, perhaps Table 1 Selected demographic and clinical features of subjects participating in the Lead-in phase of the HALT-C trial, the genetics ancillary study, and in the current report…”
Section: Discussioncontrasting
confidence: 68%
“…Although neither the IL10À1082 nor the IL10À592 promoter polymorphism alone predicted response to treatment, the IL10 ACC/ACC diplotype was associated with SVR and this association was relatively strong, especially after adjustment for other predictors of SVR. We also note that the frequency of ACC/ACC diplotype among the HALT-C population (5.8%) was lower than that observed in the general adult population by Trompet (7.3%), Gowans (7.8%) and Klein (10%) [28][29][30] suggesting that subjects with this diplotype were underrepresented in the HALT-C cohort, perhaps Table 1 Selected demographic and clinical features of subjects participating in the Lead-in phase of the HALT-C trial, the genetics ancillary study, and in the current report…”
Section: Discussioncontrasting
confidence: 68%
“…Although Gowans et al . showed no relationship between IL‐10 ‐1082, ‐819, and ‐592 polymorphisms and disease progression in MDS, the present study showed that the IL‐10 high producer type (GCC/ACC or ACC/ACC haplotype, ‐819CC and ‐592CC genotype) was significantly associated with poor survival and leukemia progression. The frequency of polymorphism of the IL‐10 promoter in different races may affect the different influence.…”
Section: Discussioncontrasting
confidence: 49%
“…Além disso, vários outros trabalhos de associação entre o sistema HLA e leucemias foram realizados por autores em vários países, com resultados variáveis [14][15][16][17][18] .…”
Section: Discussionunclassified